A Cosmological Reformulation of Anselm's Proof That God Exists - Campbell, Richard, author.
1 online resource.
Keywords: In this book, Richard Campbell reformulates Anselm's proof to show that factual evidence confirmed by modern cosmology validly implies that God exists. Anselm's proof, which was never the "ontological argument" attributed to him, emerges as engaging with current philosophical issues concerning existence and scientific explanation. Because every observable thing has a beginning, it can be deduced that there is always in reality something than which a greater cannot be thought, which exists necessarily. It follows that its non-existence is inconceivable. Anselm then proves that this is the God in whom he believes, who alone so truly exists that He could not be thought not to exist. The contingent nature of the universe is therefore a consequence of the proven belief that God is the Creator of everything else.